Factors associated with non-initiation of mental healthcare after detection of poor mental health at a scheduled health check: a cohort study. Issue 10 (16th October 2020) - Geyti, Christine; Christensen, Kaj Sparle; Dalsgaard, Else-Marie; Bech, Bodil Hammer; Gunn, Jane; Maindal, Helle Terkildsen; Sandbaek, Annelli
Abstract : Introduction: Poor mental health is an important public health concern, but mental health problems are often under-recognised. Providing feedback to general practitioners (GPs) on their patients' mental health status may improve the identification of cases in need of mental healthcare. Objectives: To investigate the extent of initiation of mental healthcare after identification of poor mental health and to identify factors associated with non-initiation. Design: Prospective cohort study with 1-year follow-up. Setting: In a population-based health preventive programme, Check Your Health, we conducted a combined mental and physical health check in Randers Municipality, Denmark, in 2012–2015 in collaboration with local GPs. Participants: Participants were 350 individuals aged 30–49 years old with screen-detected poor mental health who had not received mental healthcare within the past year. The cohort was derived from 14 167 randomly selected individuals of whom 52% (n=7348) participated. Mental health was assessed by the mental component summary score of the 12-item Short-Form Health Survey. Outcome: The outcome was initiation of mental healthcare. Mental healthcare included psychometric testing by GP, talk therapy by GP, contact with a psychologist, contact with a psychiatrist and psychotropic medication. Results: Within 1 year, 22% (95% CI 18 to 27) of individuals with screen-detected poor mental health initiated mental healthcare. Among individuals who initiated mental healthcare within follow-up, one in six had visited their GP once or less in the preceding year. Male sex (OR: 0.49 (95% CI 0.28 to 0.86)) and less impaired mental health (OR: 0.93 (95% CI 0.89 to 0.98)) were associated with non-initiation of mental healthcare. We found no overall association between socioeconomic factors and initiating mental healthcare. Conclusion: Systematic provision of mental health test results to GPs may improve the identification of cases in need of mental healthcare, but does not translate into initiation of mental healthcare. Further research should focus on methods to improve initiation of mental healthcare, especially among men. Trial registration number: NCT02028195 .